Optimización de la cadena logística en la exportación de frutas para mejorar la eficiencia en C.I Atlantic Export and Imports Ltda (2024)
C.I ATLANTIC EXPORT AND IMPORTS LTDA, is a fruit export company based in Apartado, Antioquia, with this project we propose to comprehensively improve the logistics chain of fruit exports in this company. From the detailed recognition of the process to the implementation of technological and strategic solutions, we seek to enhance the operational efficiency and competitiveness of the company in the international market